Caracterização químico-mineralógica e transformação termal das fases dos aglomerados de níquel laterítico de onça-puma, província mineral Carajás (PA). influência metalúrgica - SILVEIRA, Rosinaldo Fonseca da (2020)
Lateritesof saprolytic nickel are fed to the RKEF process (Rotary Kiln - Electric Furnace) for the production of ferro-nickel alloys. During the calcination, drying and reduction operations, powdery materials are produced that are not suitable to remain in the operating circuit, so they are removed from the metallurgical process, agglomerated and vacuum extruded for later on the production line. Agglomeration and subsequent extrusion produces cohesive blocks with granulometry and shape suitable for use in metallurgical processes, promoting an increase in the efficiency of the industrial operation. In this paper studies of chemical, physical and mineralogical characterization of the constituents of these agglomerates were carried out, in order to evaluate the behavior of the mineral phases during the drying and calcination operations, and thus contribute to the understanding in the pyrometallurgical process of obtaining ferro-nickel alloys. The characterization involved mineralogical tests by X-ray diffraction (XRD), chemical tests by X-ray fluorescence (FRX), thermal by thermogravimetry (TG) / Differential Scanning Calorimetry (DSC), as well granulometric and morphological by Scanning Electron Microscopy (SEM). Nickel agglomerates consisting of aggregates of powdery material with particle sizes less than 100 µm and morphologically comprised of sub-leased grains and mineralogically composed of lizardite-chrysolite, as the main nickel-bearing phases, as well as trivorite, clinochlore and quartz. In these extrudad, SiO2, Fe2O3 and MgO are predominant and correspond to the group serpentine, being similar to the mineral phases present in the ROM fed to the RKEF process and indicate the saprolytic origin of the mineral. When the heat treatment, of the agglomerates was carried out, the hydrated compounds of the lateritic nickel ore were the ones that presented the main changes in its crystalline structure, favoring the formation of the forsterite, hematite, trevorite and enstatite phases. The formation of forsterite and trevorite enstatite has a deleterious effect on the reduction, of the ore, which may generate greater energy demands during this operation.